2021
DOI: 10.1109/tc.2020.2997555
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Security Dependence for Conditional Speculation Against Spectre Attacks

Abstract: Speculative execution side-channel vulnerabilities such as Spectre reveal that conventional architecture designs lack security consideration. This paper proposes a software transparent defense framework, named as Conditional Speculation, against Spectre vulnerabilities found on traditional out-of-order microprocessors. It introduces the concept of security dependence to mark speculative memory instructions which could leak information with potential security risks. More specifically, security-dependent instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Ref. [ 16 ] proposed a software protection method (Conditional Speculation) that limited the execution of memory instructions, which could resist attacks based on Spectre vulnerabilities. However, this method cannot prevent attackers from stealing branch information or monitoring the CFI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [ 16 ] proposed a software protection method (Conditional Speculation) that limited the execution of memory instructions, which could resist attacks based on Spectre vulnerabilities. However, this method cannot prevent attackers from stealing branch information or monitoring the CFI.…”
Section: Discussionmentioning
confidence: 99%
“…Members of our lab have previously proposed various hardware security protection methods for embedded systems [ 11 , 12 , 13 , 14 , 15 ], but when applied, it was found that attackers could still exploit the vulnerabilities of BPUs to perform attacks. Therefore, we began to refer to existing methods [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [15] proposed a software protection method (Conditional Speculation) that limited the execution of memory instructions, which could resist attacks based on Spectre vulnerabilities. However, this method cannot prevent attackers from stealing branch information or monitor the CFI.…”
Section: Comparison With Other Security Protection Methodsmentioning
confidence: 99%
“…Although the resource overhead of this method is low, it is difficult to balance the protection capability and performance overhead due to the simple mechanism of identifying spy processes. Conditional Speculation [15,23] dynamically identified dangerous access instructions by implementing different filtering mechanisms, but had a high performance overhead for some test programs. BRB [24] prevented malicious data injected by attackers from being used by assigning separate branch history tables (BHTs) to different programs, but had a high resource overhead and could not provide the effective protection for the shared parts.…”
Section: Prevent Obtaining the Execution Status Of Branchesmentioning
confidence: 99%
See 1 more Smart Citation